Seasonal fluctuations attenuate stimulatory or inhibitory impacts of colonial birds on abundance, structure and diversity of soil biota - Pen-Mouratov, Stanislav; Dayan, Tamar (Frontiers in Microbiology, 2023)
The soil microorganisms and free-living nematodes, was investigated in association with the nesting and roosting habitats of the following piscivorous and omnivorous colonial birds: black kite (Milvus migrans), great cormorant (Phalacrocorax carbo), black-crowned night heron (Nycticorax nycticorax) and little egret (Egretta garzetta), in Israel’s Mediterranean region. Abiotic variables, abundance, trophic structure, sex ratio and genus diversity of soil free-living nematodes, and total abundance of bacteria and fungi, were measured during the wet study period, following our previous study, which was conducted during the dry period. The observed soil properties were important drivers influencing the soil biota structure. Presence of the most crucial nutrients for plants and soil organisms, such as N and P which limit primary productivity in many ecosystems worldwide, was strongly dependent on the diet of the compared piscivorous and omnivorous bird colonies; levels of these nutrients were notably higher in the bird habitats than in their respective control sites during the study periods. The applied ecological indices indicated that the different species of colonial birds can have different (stimulatory or inhibitory) impacts on abundance and diversity of the soil biota, affecting the structure of the soil free-living nematode population at the generic, trophic and sexual levels during the wet study periods. Our results illustrated that the seasonal fluctuations could change, and even attenuate the effect of bird activity on the abundance, structure and diversity of the soil communities.